Towards co-management of small-scale inland fisheries and livelihoods : a case study of Lake Itezhi-Tezhi, Zambia - Kapembwa, Sydney (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.